Sharing Arctic Science:Applying the Common Heritage and Common Concern of Humankind in the Arctic - Dervovic, Medy (2022)
Addressing climate change effectively and efficiently requires a more in-depth under- standing of its impacts and the interrelationships between climate patterns around the world. Given the magnitude of climatic and oceanic changes in the Arctic, marine scientific research in this region is of particular interest to humankind as it would improve mitigation and remediation strategies. The application of the Common Heritage and Common Concern of Humankind principles to Arctic Science aims at enhancing international scientific cooperation in the Arctic and generalizing the shar- ing of Arctic Scientific Data and Results. Despite exhibiting inherent conceptual limi- tations, both concepts show potential to legally and inclusively frame the Sharing of Arctic Science for the benefit of humankind. Moreover, this application contributes to the debate on a sui generis concept reflecting the need to face future challenges of climate change for the sake of humankind.